Analisis Kendala Pengembangan Pertumbuhan Produksi Perusahaan Semen dan Struktur Keuangan terhadap Kinerja SCM di Periode Pandemi - Fuad Syamlan, Adiba; Soelistya, Djoko; Ilham, Rachmad (Program Studi Manajemen Universitas Muhadi Setiabudi, 2023)
The success of companies in today's global competition is strongly influenced by their ability to utilize resources. In our country, which has an open market system with government linkages through the customs and excise department of state-owned enterprises, development is very rapid. Management teams in the project business are faced with the challenge of making choices and decisions that support desired goals, even though change often complicates their task. Researchers make earlystage observations to obtain data and manage it to show the progress of achievement in each buyer's transaction during a certain period. In managing a business, there are two competing theories, namely maximizing producer surplus and maximizing stakeholder surplus. Both of these theories can be alternatives that compete or complement each other. It is important for companies to understand and implement expansion, which is the expansion of the company's territory by occupying other areas either partially or wholly. This aims to achieve efficiency, gain higher profits, and remain competitive. This study uses a combination of qualitative and quantitative methods, with a focus on the effect of changes in work pattern systems on improving company performance and profits. The results of the study show that changes in work pattern systems have a positive impact on companies, increasing activities and the range of products offered. These changes also affected the performance of all employees in the marketing division and the company as a whole. In order to reach a conclusion, this study confirms that the change in the work pattern system is more profitable than the previous pattern system, because it has brought development to the company with a positive influence on performance and profits, as well as affecting the overall company turnover.